2019
DOI: 10.1002/jmv.25537
|View full text |Cite
|
Sign up to set email alerts
|

Cosmopolitan A1 lineage of dengue virus serotype 2 is circulating in Pakistan: A study from 2017 dengue viral outbreak

Abstract: Dengue viral infection has become a challenge in tropical and subtropical countries where dengue virus is endemic. Its epidemics are occurring at higher rates amid its circulation throughout the year. Since the first documented outbreak in Pakistan in 1994, this region has reported many sporadic cases and epidemics. There is availability of small scale demographic and epidemiological studies on dengue viral infection in Pakistan. The year 2017 witnessed a huge dengue outbreak in Peshawar city of Pakistan with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…Recent studies have reported that dengue virus infection is endemic in Pakistan, where the highest incidences have been reported in the monsoon season 11 , 12 . Previously, three major outbreaks have been reported (in 2006, 2010, and 2011) with more than 40,000 individuals in the country 13 , 14 . In 2011, a huge outbreak of dengue was experienced in Lahore in which the dual serotype infections increased the number of cases and related mortality 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that dengue virus infection is endemic in Pakistan, where the highest incidences have been reported in the monsoon season 11 , 12 . Previously, three major outbreaks have been reported (in 2006, 2010, and 2011) with more than 40,000 individuals in the country 13 , 14 . In 2011, a huge outbreak of dengue was experienced in Lahore in which the dual serotype infections increased the number of cases and related mortality 15 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on DENV-4 circulating in Pakistan [27, 28], although the present small-scale study does not detect any case in 2022. There have been several reported shifts in dengue virus serotypes, genotypes, or lineages that have resulted in increased severity of dengue infection[11, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…The Metro-Bus project in Peshawar was identified as a major factor through this analysis since the hotspots lie close to the project areas. [70]. Construction on smaller scale is equally dangerous as there are diggings involved and water accumulation results in spread of disease.…”
Section: Discussionmentioning
confidence: 99%